Serotonin Syndrome: A Clinical Case Report - Alshmandi, Mohamed; Butt, Haider Ali Tariq; Kiernan, Julia (Scripta Medica, 2025)
Serotonin syndrome is characterised by high levels of serotonin, a neurotransmitter, in the nervous system. A 36-year-old male was hospitalised due to generalised weakness, loss of appetite, jaundice, abdominal pain, recurrent fever and delirium. Diagnoses of serotonin syndrome, peptic ulcer disease and metabolic-associated fatty liver disease (MAFLD) were confirmed. Management required withdrawal of the causative agent and administration of intravenous fluid support and benzodiazepines to control agitation and neuromuscular symptoms. This case clearly demonstrates the critical importance of thorough history-taking, careful clinical examination and reassessment of provisional diagnoses when initial treatments prove ineffective.